Toward a technology community in the learning sciences - Aleahmad, Turadg; Slotta, James D.; Kyza, Eleni A. (My University, 2009)
CSCL research and implementation depend critically on technology development, yet the process of development is not much discussed in a research context. This panel is aimed at helping the CSCL community think more critically about how it develops technology and uses it. Researchers in the learning sciences must be able to use technology with agility in order to create materials, manage complex pedagogical structures, collect data, analyze complex patterns, and report their findings. They must be able to exchange these materials in order to promote replication and innovation in the field. Finally, they must connect their materials to the public discourse on standards, re-use, and open source licensing. It is to our advantage as a field if we move toward a more coherent set of practices and internal standards regarding our own uses of technology. Further, we must enable our young investigators to get involved in such research, reducing the absurd level of collaborative and development overhead that currently confronts them. The average level of human resources that are available to any investigator in the field are certainly less than one full-time programmer – most likely closer to a quartertime programmer. How can we enable investigators to move forward confidently in their research with such limited staff for developing technology infrastructure for their research? This panel is proposed to discuss various efforts that have been made and are currently underway to address this matter, and to engage the community in a discussion about the nature of the problem. We will look at this problem through the themes of re-use, adaptability, easy of use and interoperability. The panel and audience will debate the costs and benefits of designing towards these goals and specific potential remedies such creating and participating in an open-source community of education research technology development. Is it reasonable to aspire to the creation of a commons of education research software components that can be set up and configured by any technology specialist in a short amount of time? Can they be made simple enough to configure and to author new materials and activities that a graduate student with some technical orientation could learn to do so without distracting from their research questions? As a field, we have several prominent examples of large-scale efforts to develop scalable, reusable, interoperable software, which have met with some limited success. There are many reasons why previous efforts haven't resulted in an easy-to-use framework for new investigators, and these will be discussed by the panel. Perhaps more interesting, there are new emerging technologies and philosophies that may help our efforts become more successful. The goal of this panel is to understand the problems confronting our community in relation to technology frameworks and to begin articulating some of the possible solutions or responses to those problems. To that end, we also address the issue of technology developers as a valuable element of our intellectual community. As the world of technology evolves, it offers new insight into the powerful mechanisms of collaboration, aggregation of knowledge, community, social and semantic networking. Researchers are captivated by the new metaphors of Web 2.0, the promise of open source and open content, and new forms of human computer interaction made popular by the Wii, the iPhone and multi-touch surfaces. Yet it is our technology specialists who lead the way in developing such innovations. In the past ten years, our technology staff have shifted from being "programmers who implemented our designs" to being co-designers and even colleagues. This is an exciting development, pointing to new intellectual capacity in our field that must be CSCL2009 MAIN CONFERENCE EVENTS - PANELS © ISLS 13 supported. This panel will recognize the opportunities that could come from nurturing a community of technology developers, who might otherwise work in isolation – helping them connect with peers, exchange ideas, and co-develop common resources.
Keywords: Technology; Science